Optimizing the Digital Marketing Strategy of PT Sewu Segar Primatama through Instagram @rejuveid - Wigustira, Monica Putri; Prihantoro, Edy (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study aims to explore the digital marketing strategy employed by PT Sewu Segar Primatama, specifically through its Instagram account @rejuveid, for marketing its cold-pressed juice products in Indonesia. The research investigates how the company has adapted its marketing communication strategy in response to changing market dynamics. Results: The findings indicate that PT Sewu Segar Primatama has shifted its marketing communication from traditional methods to digital platforms, particularly Instagram, in response to emerging market trends. The company has optimized its marketing efforts to align with consumer behavior, leveraging Instagram’s capabilities to engage with the audience. Findings: The study highlights that PT Sewu Segar Primatama has effectively used Instagram to engage consumers at various stages of the AISAS communication model (Attention, Interest, Search, Action, Share). The company’s approach incorporates educational content and interactive campaigns to maintain consumer interest. Novelty and Originality: This research contributes to the growing body of knowledge on digital marketing strategies, particularly in the FMCG sector, by offering insights into how brands can optimize Instagram for effective communication and engagement. Conclusion: PT Sewu Segar Primatama’s shift to digital marketing through Instagram has proven to be a successful strategy in adapting to changing consumer needs, demonstrating the effectiveness of social media in modern marketing communication. Type of paper : Empirical Research Paper